Does VIX Offer Timing Possibilities in Equities' Sector and Style Rotation - Keränen, Niklas (My University, 2017)
VIX is often referred as an investor’s fear gauge. This thesis concentrates on whether the relative VIX levels can be used as a market timing signal for equities. Giot (2005) finds that high (low) relative levels of VIX always lead into positive (negative) returns for S&P 100, no matter what the holding period is. In this thesis equities are divided into 10 industries and Fama and French (2015) five factor portfolios are also used in order to find whether volatility drives the returns of these portfolios. Fama-French portfolios are Market portfolio, SMB (small cap stocks minus large cap stocks), HML (value stocks minus growth stocks), RMW (high operating profitability stocks minus low operating profitability stocks) and CMA (conservative stocks minus aggressive stocks). This thesis covers data from 29th January 1993 until the end of 2015. In order to define VIX levels, a 500-day rolling method is used to rank each day’s close value for VIX. Ranks are always based on the previous 500-day history of VIX values. High negative correlation between VIX and equities are also under consideration. This thesis shows that the closer the observations are on the present day, the higher the negative correlation tend to be. Results reveal that highest levels of VIX are great at signaling positive future returns. These returns are above average and significant in most of the cases. On the other hand, industries that are less negatively correlated with VIX tend to have better returns on lower volatility levels. Volatility also seems to be driving Fama-French factor returns. Especially results from SMB and HML portfolios are distinctive, but CMA portfolio seem to be affected by volatility too. Small cap stocks perform better on lower volatility levels while large cap stocks perform better on higher volatility levels. Growth stocks outperform (underperform) value stocks on higher (lower) volatility levels. Conservative stocks outperform (underperform) aggressive stocks on lower (higher) volatility levels.
Keywords: VIX; market timing; Fama-French 5 factors; negative correlation; fi=Laskentatoimi ja rahoitus|en=Accounting and Finance|; fi=Master's Degree Programme in Finance|